Intention To Adopt Activity-Based Costing In Jordanian Manufacturing Industry - Ibrahim, Yousef Ammar Ali (2023)
Activity-Based Costing (ABC) adoption and implementation have been widely researched in developed countries. However, in developing countries like Jordan, research regarding these issues in general, and within the Jordanian manufacturing shareholding companies in specific, is still limited. The present research attempts to increase the understanding of ABC adoption in Jordanian manufacturing shareholding companies. In this wake, the current study has examined the factors influencing the adoption of ABC in the Jordanian manufacturing industry. Thus, this study investigates the impact of innovation & technology, cost structure, top management commitment, and competition towards the adoption of ABC in the manufacturing sector of Jordan. Moreover, this study evaluated the mediating effect of adoption of ABC between the relationships of innovation & technology, cost structure, top management commitment, competition, with Firm Performance. Finally, this study tries to assess the moderating effect of organizational culture in the relationships of adoption of ABC and firm performance. The theoretical framework of this study is based on the contingency theory and diffusions of innovation theory. The sample of this study was the Jordanian manufacturing industry across Jordan and was identified through Stratified random sampling. A total of 201 data was collected based on the assigned strata. Data analysis was done using Smart PLS version 3.2.8 and SPSS version 23.0.